The effect of cycling shoes and the shoe-pedal interface on maximal mechanical power output during outdoor sprints. (1st September 2020) - Burns, Andrew C.; Kram, Rodger
Abstract: Cyclists and industry professionals believe that cycling shoes with pedal attachment and stiff soles improve performance. However, scientific evidence has demonstrated that cycling shoes have no significant effect on metabolic cost during low-intensity, submaximal, steady-state cycling (50–150 W). Here, we investigated if stiff-soled cycling shoes combined with clip-in pedals provide benefits relevant to sprint cycling. We measured the mechanical power outputs and velocities of twelve healthy male cyclists during maximal sprint cycling. Participants rode outdoors on a paved asphalt road with a steady, uphill gradient of 4.9%. Each participant completed sets of three 100-metre cycling sprints in three conditions: (1) running shoes with flat pedals (no pedal attachment + flexible soles), (2) running shoes with classic aluminium quill pedals with toe clips and straps (pedal attachment + flexible soles), and (3) cycling shoes with clip-in pedals (pedal attachment + stiff soles). When using the running shoes, the toe clip attachment increased maximum sprint power by 9.7 ± 8.7% ( p = 1.7E − 03). Maximum sprint power was 16.6 ± 10.2% ( p = 3.25E − 06) greater for the stiff-soled cycling shoes combined with clip-in pedals compared to the flexible running shoes with toe clips condition, presumably due to the greater sole stiffness of the cycling shoes. Shoe-pedal attachment and stiff soles each positively improve cycling performance during high-power, uphill sprints.